Deployment and Coverage Analysis of Typical Large-Scale LEO Communication Constellations - RUAN Yongjing; HU Min; XUE Wen (天地一体化信息网络)
Low Earth Orbit (LEO) large-scale communication constellations have emerged as a focal point in communication due to their substantial scale and rapid deployment capabilities. Among these constellations, Starlink and OneWeb have successfully offered broadband Internet services. This paper centers on these two representative constellations. Firstly, an overview of their current development status is provided. Subsequently, Starlink is examined in detail, focusing on its orbital layered design and deployment strategies, while an analysis of its coverage performance and potential commercial applications is conducted. Next, OneWeb's deployment model, coverage efficiency, and existing commercial applications are explored. Finally, a summary of the similarities and differences between Starlink and OneWeb is presented, and a forecast of the future development trends of LEO large-scale communication constellations is offered.